Asterix and the golden sickle - Goscinny, Rene; Uderzo, Albert (Orion London, 2004)
Astérix and his gang are in search of a golden sickle to replace the one that Getafix has broken. Unfortunately the sicklesmith, who is a cousin of Obelix's, has mysteriously disappeared